Persatuan Seni khat Kebangsaan (PSKK) 1985 - 2009: its contributions and styles to the Contemporary Islamic Art in Malaysia / Sallehuddin Mohamed - Mohamed, Sallehuddin (2014)
The establishment of the National Islamic Calligraphy Art Association in 1985 also known as Persatuan Seni Khat Kebangsaan (PSKK) was the result of the decline in the usage of 'jawi' script and the introduction of the National Cultural Congress 1971. The 'jawi' was derived from Arabic script using the Malay alphabets and pronunciations. The main objectives of PSKK are to preserve the 'jawi* script and to educate the general public the correct method of writing according to the order of the classical Islamic calligraphy. To date, there is no in depth research has been done on the 28 years of existence of PSKK, its contributions and styles to the contemporary of Islamic art in Malaysia. The research used the historical and exploratory approach in analyzing the data. The analysis is on the form, styles and content based on the Al- Qur'an, Al-Hadith, Malay traditional heritage and culture. PSKK had and still contributes to the development of contemporary Islamic art in Malaysia. Four basic components of PSKK styles composed of idea, tools, form and content which are inter-related. The styles and content manifested by the PSKK artists were well received by the general public. It is undeniable to state that the PSKK's contributions to the development of Contemporary Islamic Art in Malaysia is of utmost importance. It reflects the identity of Malaysia forms and meaning in Islamic culture as a whole.